Structure recognition and fluid flow potential based on well data and geological field investigations. A case study of the Istebna Beds, Silesian Unit, Carpathians - Krakowska-Madejska, Paulina; Puskarczyk, Edyta; Starzec, Krzysztof; Jarzyna, Jadwiga; Stadtműller, Marek (Geology, Geophysics and Environment, 2024)
Facies were recognized based on the results of well logging data, using these measurements and conducting a comprehensive interpretation. This was done by first using shaliness (volume of shale) as the main parameter for a geological profile division into petrophysical lithofacies before secondly calculating the Flow Zone Index (FZI), utilizing porosity and permeability estimated from well logging interpretation and defining Rock Types on the basis of FZI frequency distributions. FZIs were also determined according to porosity and permeability from laboratory measurements whenever the results were available. Descriptions of cores and cuttings together with the results of geological field investigations were the basis for lithofacies determination. Maps of average porosity, permeability, and FZI values were constructed for the study area. Three types of facies data and maps of reservoir parameters were used to support the recognition of geological structures and their assessment of the potential for fluid movement in the rock formation. The facies analyses were performed on the example of the Istebna Beds of the Silesian Unit in the Carpathians.